To determine the factors that influence customer buying behaviour (Generation Y) towards purchasing Amanah Saham Nasional Berhad (ASNB) products / Mohammad Iskandar Karib and Nor Ain Nadia Zamran - Karib, Mohammad Iskandar; Zamran, Nor Ain Nadia (Faculty of Business and Management, 2014)
All companies need strategies in order to survive or to become a leader in the market nowadays, therefore a research study towards finding the suitable strategies for Amanah Saham Nasional Berhad had been carried out. This research attempts to determine the influence of the independent variables (financial literacy, family background, and Syariah compliance) on the Gen Y buying behaviour towards purchasing ASNB products. Survey questionnaires were distributed to the students of UiTM Malacca City Campus, Malacca. A Likert Scale has been formed in the questionnaire. The results of the research were obtained by using three methods of analysis which are frequency distribution, reliability test, and Pearson correlation. Furthermore, the process of analyzing and interpreting the data was being presented through tables. Eventually, the results of this study showing that family background is the most influential factor that contributes the Gen Y buying behavior towards purchasing ASNB products.